Absorption of iron from Tegillarca granosa using an in vitro simulated digestion and Caco‐2/HepG2 co‐culture system. (3rd October 2022) - Sun, Bolun; Zhang, Panxue; Zhang, Jinjie; Huang, Tao; Li, Chao; Yang, Wenge
Abstract : Background: Iron‐deficiency anemia is one severe micronutrient malnutrition and has captured worldwide attention. This study evaluated the in vitro iron absorption of two iron‐binding proteins (hemoglobin and ferritin) from Tegillarca granosa . In addition, the protein structure–iron absorption relationship and the regulatory effect of hepcidin on cellular iron absorption were explored. Results: Our findings revealed that both hemoglobin and ferritin extracted from T. granosa contained abundant iron‐binding sites, as evidenced by stronger peaks in amide I and II regions compared with the two proteins from humans. Less β ‐sheet (27.67%) structures were found in hemoglobin compared with ferritin (36.40%), probably contributing to its greater digestibility and more release of available iron. This was confirmed by the results of Caco‐2/HepG2 cell culture system that showed iron absorption of hemoglobin was 26.10–39.31% higher than that of ferritin with an iron content of 50–150 μmol L −1 . This high iron absorption of hemoglobin (117.86–174.10 ng mg −1 ) could also be due to more hepcidin produced by HepG2 cells, thereby preventing ferroportin‐mediated iron efflux from Caco‐2 cells. In addition, the possible risk of oxidative stress was evaluated in cells post‐iron exposure. In comparison with ferrous sulfate, a common iron supplement, Caco‐2 cells treated with the iron‐binding proteins had a 9.50–25.73% lower level of intracellular reactive oxygen species, indicating the safety of hemoglobin and ferritin. Conclusion: Collectively, the data of this research would be helpful for understanding the key features and potential of developing hemoglobin and ferritin from T. granosa as novel iron supplements. © 2022 Society of Chemical Industry.